The Pedagogical Character of Pederasty in Ancient Greece in the Light of Selected Gifts - Grancow, Patryk (Vade Nobiscum, tom XXII/2021: Studia z wieków dawnych, 2021)
Pederasty occurring in ancient Greece, was an essential element of its culture and identity. It had a considerable influence on the formation of the society of ancient Greece. The entire institution of pederasty had some specific framework and rules of functioning, but this article mainly focuses on the issue of giving gifts to eromenos by erastes. Selected examples of historical sources help in the correct interpretation of the gifts, their meaning, reasons and circumstances, in which they were given to the lover. This allows the discovery of the pedagogical and educational nature of pederasty and its impact on Greek society.